2019
DOI: 10.1089/aid.2018.0221
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Drug Resistance of HIV-1 Circulating in North Sulawesi, Indonesia

Abstract: Manado, the capital city of North Sulawesi, is a unique region in Indonesia because of its religion. We collected peripheral blood samples from 63 individuals on antiretroviral therapy. The amplification of viral genomic fragments, viral subtyping, detection of HIV drug resistance-associated mutations (DRAMs), and phylogenetic analyses were performed. Viral subtyping revealed that the most prevalent HIV type 1 (HIV-1) subtype/circulating recombinant form (CRF) was CRF01_AE (84.1%), followed by subtype B (6.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…All treatment failure subjects harbored resistance to NRTI and NNRTI, which are first-line ARV drugs. The pattern is concordance to a recent report from North Sulawesi, Indonesia [47]. The figure is higher than that reported in South Africa [48].…”
Section: Discussionsupporting
confidence: 92%
“…All treatment failure subjects harbored resistance to NRTI and NNRTI, which are first-line ARV drugs. The pattern is concordance to a recent report from North Sulawesi, Indonesia [47]. The figure is higher than that reported in South Africa [48].…”
Section: Discussionsupporting
confidence: 92%
“…Prior studies found relatively low rates of transmitted drug resistance in Indonesia. 22,23 Our prevalence of drug resistance in treatment-experienced individuals (5/30, 16.7%) was within the range of previous reports (6% in Papua 24 and 23.7% in North Sulawesi 25 ). Lack of clinician awareness of drug resistance in four of five subjects suggests a need for expanded access to resistance testing in addition to closer monitoring of clinical manifestations, CD4 count, and viral load to optimize management strategies.…”
Section: Discussionsupporting
confidence: 85%
“…HIV type 1 (HIV-1) is the major causative agent of HIV disease discovered in Indonesia, with more HIV-1 cases being reported in the Eastern part of Indonesia. [3][4][5][6][7][8] Papua and West Papua are two provinces with the highest rates of HIV-1 (1.34 -2.41%) in Indonesia. 9 Bali, Nusa Tenggara, and Sulawesi are three islands in the Eastern part of Indonesia in which the epidemic of HIV-1 infection continues to grow due to the high numbers of men who have sex with men (MSM), injecting drug users (IDUs), and commercial sex workers in these areas.…”
Section: Textmentioning
confidence: 99%
“…9 Bali, Nusa Tenggara, and Sulawesi are three islands in the Eastern part of Indonesia in which the epidemic of HIV-1 infection continues to grow due to the high numbers of men who have sex with men (MSM), injecting drug users (IDUs), and commercial sex workers in these areas. [4][5][6] However, there are more provinces in Indonesia without properly recorded data on HIV-1 epidemiology.…”
Section: Textmentioning
confidence: 99%
See 1 more Smart Citation